IMPLEMENTASI APLIKASI EDMODO SEBAGAI EFEKTIVITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DI MI AZZAINIYAH II GRINTING PAITON PROBOLINGGO - Niken Septantiningtyas; Nadiya Rosmila; Warda Maghfiroh Husein (Institut Agama Islam Negeri Kediri, 2021)
Abstract: The spread of pandemic in the world, especially in Indonesia, has disrupted all sectors including the education sector. The existence of social distancing due to the spread of the Covid-19 virus requires humans to maintain a distance from one another. For this reason, in order for education to continue, the government has established learning activities from home which is known as online learning. Online learning functions as a liaison between teachers and students so that they can continue to carry out teaching and learning activities. One of the applications that can be used in online learning is the Edmodo application, a learning platform based on social networks that can be downloaded easily on the Google Playstore or the APP market application on an Android device. This study aims to determine the implementation of the Edmodo application in MI Azzainiyah. The research subjects were students at MI Azzainiyah Paiton. This research uses descriptive qualitative research, which explains how the Edmodo application is applied in the institution. Abstrak: Mewabahnya pandemi di dunia, terutama di Indonesia membuat semua sektor terganggu termasuk sektor Pendidikan. Adanya social distancing akibat merebaknya virus covid-19 mengharuskan manusia menjaga jarak antar satu dengan yang lain. Untuk itu, agar pendidikan tetap berlangsung, pemerintah menetapkan pembelajaran dari rumah yang dikenal dengan pembelajaran daring. Pembelajaran daring berfungsi sebagai penghubung antaraÂ guru dan siswa agar tetap bisa melakukan kegiatan belajar mengajar. Salah satu aplikasi yang dapat digunakan dalam pembelajaran daring adalah aplikasi edmodo, salah satu platform pembelajaran yang berbasis jejaring sosial yang dapat didownload dengan mudah di google playstore ataupun aplikasi APP market pada perangkat android. Penelitian ini bertujuan untuk mengetahui implementasi aplikasi edmodo di MI Azzainiyah. Subjek penelitian adalah peserta didik MI AzzainiyahÂ Paiton. Penelitian ini menggunakan penelitian kualitatif deskriptifÂ yaitu menjelaskan bagaimana penerapan aplikasi edmodo di lembaga tersebut.